2005
DOI: 10.1007/s00464-004-8825-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum ghrelin predict weight loss after Roux-en-Y gastric bypass in rats

Abstract: Using our recently developed rat model of RYGB, we found that postoperative weight loss is correlated with the magnitude of the decrease in circulating ghrelin levels. This correlation provides the strongest evidence to date that altered ghrelin signaling contributes to weight loss after this operation. The lower level of circulating ghrelin after RYGB likely blunts the appetitive drive, leading to decreased food intake in these animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…Many studies have shown gastric bypass operations to be associated with significant reduction of ghrelin levels (Cummings et al, 2002a;Geloneze et al, 2003;Lin et al, 2004;Roth et al, 2009;Stylopoulos et al, 2005;Suzuki et al, 2005). In addition, the normal, meal-related fluctuation and the diurnal rhythm of ghrelin level was found to be absent after gastric bypass surgery (Cummings et al, 2002a).…”
Section: Ghrelin and Bariatric Surgerymentioning
confidence: 99%
“…Many studies have shown gastric bypass operations to be associated with significant reduction of ghrelin levels (Cummings et al, 2002a;Geloneze et al, 2003;Lin et al, 2004;Roth et al, 2009;Stylopoulos et al, 2005;Suzuki et al, 2005). In addition, the normal, meal-related fluctuation and the diurnal rhythm of ghrelin level was found to be absent after gastric bypass surgery (Cummings et al, 2002a).…”
Section: Ghrelin and Bariatric Surgerymentioning
confidence: 99%
“…PYY and GLP-1 are satiety signals released by the endocrine L cells of the gastrointestinal tract after meals that have been shown to reduce food intake and body weight gain in obese Zucker rats [43][44][45]. In humans, fasting and post-prandial plasma levels of PYY increase progressively 6 and 12 months after vertical banded gastroplasty surgery [46].…”
Section: Discussionmentioning
confidence: 99%
“…Much is known regarding life with chronically reduced ghrelin levels because thousands of individuals have undergone Rouxen-Y gastric bypass surgery, which reduces ghrelin levels by 50-70% for weeks relative to weight-loss controls. Postsurgical ghrelin levels are even lower after total gastrectomy or sleeve gastrectomy (removal of the fundus) and remain so in the long-term (34)(35)(36)(37)(38)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). The Roux-en-Y gastric bypass and sleeve gastrectomy surgeries both produce massive weight reduction, greater than those of other surgical procedures that less effectively reduce ghrelin levels and improve the health of previously morbidly obese patients with low complication rates (37,78,79).…”
Section: Resultsmentioning
confidence: 99%
“…Subchronic neutralization of the ghrelin molecule with the biostable aptamer l-NOX-B11-2, an l-RNA-spiegelmer based therapeutic, similarly reduced spontaneous food intake and feed efficiency, promoted weight loss, and reduced fat mass (31). Finally, active immunization with Nterminal-inclusive ghrelin haptens slowed weight gain and fat accrual in adult rats in direct relation to the elicited anti-ghrelin antibody response (32).Ghrelin levels increase during voluntary energy restriction (i.e., dieting); these increases predict weight regain and are thought to impede sustained weight loss (7,(33)(34)(35)(36)(37)(38), so new approaches to oppose ghrelin action may be therapeutically important. From a chemical standpoint, ghrelin is the first peptide isolated from natural sources in which the hydroxyl group of a Ser residue (Ser-3) is acylated by n-octanoic acid (3, 39).…”
mentioning
confidence: 99%
See 1 more Smart Citation